PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sembiring, Enjelina br; Sinaga, Ria Veronica (UNIKA Santo Thomas, 2020)
This study aims to determine the effect of financial performance as measured by Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return On Equity (ROE), and Earning Per Share (EPS) on stock prices at LQ45 companies listed on the Indonesia Stock Exchange. This research was conducted using secondary data with documentation techniques obtained through annual reports published on the Indonesia Stock Exchange, which can be viewed on the website www.idx.co.id. The population in this study was 45 companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The sampling technique used was the purposive sampling method. The total sample of this study was 27 companies. The data analysis technique used is multiple regression analysis techniques by performing the classical assumption test, t-test, and F test where the significance level is 5%. The results of t-test research show that CR has a negative and significant effect on stock prices, DER has a positive and significant effect on stock prices, TATO has a positive and significant effect on stock prices, ROE has a negative and significant effect on stock prices, EPS has a positive and significant effect on stock prices. The results of the F test study indicate that CR, DER, TATO, ROE, and EPS have a simultaneous and significant effect on stock prices